DQ Impedance Stability Analysis for the Power-Controlled Grid-Connected Inverter - Li, Chuanyue; Liang, Jun; Cipcigan, Liana M.; Ming, Wenlong; Colas, Frederic; Guillaud, Xavier (IEEE transactions on energy conversion, 2020)
For a grid-connected inverter requiring the ac voltage magnitude and the active power control, both vector control and power synchronization control can be applied. The stability comparison based on the dq impedance stability analysis between both control are carried out via three factors including the grid impedance, the inner current loop and the virtual impedance. The dq impedances of the inverter based on both control are derived. The determinant of the impedance ratio matrix is used for the stability analysis. The bode plot of the grid impedance and the inverter impedance are present to assist the stability analysis and explain their interactions. It is found that increasing the grid impedance and the cut-off frequency of the current loop stabilize the inverter with the power synchronization control, which is converse to the vector control. Furthermore, the inverter with the power synchronization control may suffer the instabilities when connecting to a strong grid. The virtual inductor and resistor are proposed to enhance the stability for the vector control and the power synchronization control respectively. The simulation validation using Matlab/Simulink is performed.